Peran Konselor dalam Membantu Siswa Mengatasi Stres Akademik: Pendekatan Bimbingan Konseling - Akhir Pardamean Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Academic stress is a significant problem experienced by students at various levels of education. Academic stress can have a negative impact on students' well-being and their academic performance. Individual counseling has been recognized as an effective approach in helping students overcome academic stress. This research aims to determine the role of counselors in helping students overcome academic stress: a counseling guidance approach. This research is qualitative research. The results of the analysis show that there are several individual counseling strategies that are effective in dealing with academic stress in students. These strategies include relaxation techniques, time management, developing study skills, social support, self-regulation, and developing adaptive thinking patterns. Previous research also shows that individual counseling conducted by trained and experienced counselors has a positive impact on reducing academic stress and improving student well-being. This research has important reinforcement for counseling practitioners and researchers in the field of education. By understanding effective individual counseling strategies, counseling practitioners can develop appropriate and scalable interventions to help students cope with academic stress. In addition, this research also identifies research opportunities that could provide opportunities for further research in this area.